Passive immunization of the human vagina - Deborah J. Anderson (Taylor & Francis Group, 2022)
The vagina is an excellent site for topical passive immunization, as access is relatively easy, and it is an enclosed space that has been shown to retain bioactive antibodies for several hours. A number of sexually transmitted infections could potentially be prevented by delivery of specific monoclonal antibodies to the vagina. Furthermore, our group is developing antisperm antibodies for vaginally delivered on-demand topical contraception. In this article, we describe physical features of the vagina that could play a role in antibody deployment, and antibody modifications that could affect mAb retention and function in the female reproductive tract. We also review results of recent Phase 1 clinical trials of vaginal passive immunization with antibodies against sexually transmitted pathogens, and describe our current studies on the use of anti-sperm mAbs for contraception.